Soil investigation dutch penetration test implementation of North Sumatra Polda Flat Houses - Suita, Diana; Simanjuntak, Johan Oberlyn; Lubis, Muhammad Yusuf Parlagutan; Simorangkir, Simon Petrus (Program Studi Teknik mesin, Fakultas Teknik, Universitas Al Azhar Medan, 2024)
From the results of drilling tests with machine drills, standard penetration tests (SPT), and DCPT or sondir tests, several conclusions can be taken as follows: 1). The results of boring tests show that the soil layer has medium soil consistency at a depth of 0 - 9.85 meters with NSPT value 10 – 30. 2). The soil layer consists of sandy clay, fine sand pumice stone, and fine sand. 3). Test results for the depth of solid soil at a depth of 18.6 – 19.00 meters. 4. The cone tip resistance at point S-01 is 200 kg/cm2 and S-02 is 173 kg/cm2 5). Calculation of the vertical Bearing Capacity (Qi) of the pile foundation from SPT data using a safety factor for tip penetration resistance = 3, for sticky resistance used = 5. 6). For large construction loads using deep foundations, it is necessary to check to a depth of > 10 meters or attain NSPT 60 in a row 3 times